Data from: Kin association during brood care in a facultatively social bird: active discrimination or byproduct of partner choice and demography? - Jaatinen, Kim; Noreikiene, Kristina; Merilä, Juha; Öst, Markus (Zenodo, 2012)
Intra-group relatedness does not necessarily imply kin selection, a leading explanation for social evolution. An overlooked mechanism for generating population genetic structure is variation in longevity and fecundity, referred to as individual quality, affecting kin structure and the potential for cooperation. Individual quality also affects choosiness in partner choice, a key process explaining cooperation through direct fitness benefits. Reproductive skew theory predicts that relatedness decreases with increasing group size, but this relationship could also arise due to quality-dependent demography and partner choice, without active kin association. We addressed whether brood-rearing eider (Somateria mollissima) females preferentially associated with kin using a six-year data set with individuals genotyped at 19 microsatellite loci, and tested whether relatedness decreased with increasing female group size. We also determined the relationship between local relatedness and indices of female age and body condition. We further examined whether the level of female intra-coalition relatedness differed from background relatedness in any year. As predicted, median female intra-group relatedness decreased with increasing female group size. However, the proportion of related individuals increased with advancing female age, and older females prefer smaller brood-rearing coalitions, potentially producing a negative relationship between group size and relatedness. There were considerable annual fluctuations in the level of relatedness between coalition-forming females, and in one year this level exceeded that expected by random association. Thus, both passive and active mechanisms govern kin associations in brood-rearing eiders. Eiders apparently can discriminate between kin, but the benefits of doing so may vary over time. Groupwise Coalition specific data used to clarify the connection between intragroup relatedness and group size, while controlling for breeding strategy. First column contains the year, second column ...